It's not just "us" versus "them": Moving beyond binary perspectives on intergroup processes. Issue 1 (1st January 2020) - Dixon, John; Elcheroth, Guy; Kerr, Philippa; Drury, John; Al Bzour, Mai; Subašić, Emina; Durrheim, Kevin; Green, Eva G. T.
ABSTRACT: The social psychology of intergroup relations has emerged largely from studies of how one group of people (e.g., whites) think and feel about another (e.g., blacks).  By reducing the social world to binary categories, this approach has provided an effective and efficient methodological framework. However, it has also obscured important features of social relations in historically divided societies. This paper highlights the importance of investigating intergroup relationships involving more than two groups and of exploring not only their psychological but also their political significance. Exemplifying this argument, we discuss the conditions under which members of disadvantaged groups either dissolve into internecine competition or unite to challenge the status quo, highlighting the role of complex forms of social comparison, identification, contact, and third-party support for collective action. Binary conceptualizations of intergroup relations, we conclude, are the product of specific sociohistorical practices rather than a natural starting point for psychological research.